(untitled) (International journal of medical sciences, 2026)
Diagnosis of tumors of long (tubular) bones complicated by a pathological fracture is a complex multi-stage process that requires a comprehensive clinical, instrumental and morphological approach. A pathological fracture is often the first clinical manifestation of both primary malignant bone tumors and metastatic skeletal lesions, which significantly complicates the timely verification of the diagnosis and the choice of optimal therapeutic tactics [1, 2].